PENGEMBANGAN NILAI-NILAI KESENIAN SISINGAAN UNTUK MENGATASI DISTORSI KOGNITIF - Meri Kustiawati; Mudafiatun Isriyah; Weni Kurnia Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Cognitive distortion is an inaccurate or negative thought pattern that can affect how a person views themselves, others, and the situations around them (Anisa Tunnamirah, 2025). This problem is experienced by some students of SMAIT Al-Ghazali. This cognitive distortion often causes anxiety, low self-confidence, and difficulties in learning. The specific objectives of this study are to be able to help students of SMAIT Al-Ghazali Jember to overcome cognitive distortion, contribute to making it easier for BK teachers or practitioners to provide guidance and counseling services, and so that it can be used as a guideline and reference material for further research. The values ​​contained in the sisingaan art are used as reference material for developing the Guidance and Counseling Service module. This research was conducted using the R&D (Research and Development) method, which is a development research with the ADDIE model. The output that will be produced by the researcher is a product in the form of a guidance and counseling service module in handling cognitive distortion by adopting social values ​​in sisingaan art.